Healthcare Professional’ Roles Educate Exclusive Breastfeeding: A Qualitative Exploratory Study of Strategies and Challenges - Mertasari, Luh; Duarsa, Dyah Paramita; Ani, Luh Seri; Kusuma, Anak Agung Ngurah Jaya; Bakta, I Made (YCAB Publisher, 2024)
Background:The exclusive breastfeeding program has been in place for several years, but its implementation in various countries remains suboptimal. To reduce health risks for both mothers and children, exclusive breastfeeding education should begin as early as possible during pregnancy. Objective:This study aimed to explore models of exclusive breastfeeding education during pregnancy. Method:This study used a qualitative descriptive design with an exploratory approach. The sample included all parties involved in providing exclusive breastfeeding education within the Public Health Centers working areas of Buleleng I, Sukasada I, and II. The participants comprised 35 healthcare professionals, pregnant women, postpartum mothers, and hamlet heads. Data were collected through in-depth interviews using semi-structured interview guidelines until data saturation was reached. Interviews were conducted via video calls and private messages to confirm the transcription results. Results:Thematic analysis identified three main themes: Healthcare professionals’ roles, knowledge, attitudes, and support (including multiple roles, perceptions about exclusive breastfeeding education, and formal motivation and support); Education strategy and mechanisms (encompassing educational strategies, methods, preparation, location, schedule, time allocation, content, stages, media, and effectiveness evaluation); Challenges (such as lack of knowledge, maternal circumstances, and environmental conditions). Conclusion:Public health centers should provide structured education, with midwives playing a key role in promoting exclusive breastfeeding. The delivery of education should remain flexible to accommodate various conditions. Keywords:Breastfeeding; Child; Health knowledge; Midwifery; Postpartum period